2023
DOI: 10.1021/acs.langmuir.2c02811
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation on the Dynamic Response of Ferrofluid Liquid Marbles to Steady and Pulsating Magnetic Fields

Abstract: Liquid marbles are droplets enwrapped by a layer of hydrophobic micro/nanoparticles. Due to the isolation of fluid from its environment, reduction in evaporation rate, low friction with the surfaces, and capability of manipulation even on hydrophilic surfaces, liquid marbles have attracted the attention of researchers in digital microfluidics. This study investigates the manipulation of ferrofluid liquid marbles (FLMs) under DC and pulse width-modulated (PWM) magnetic fields generated by an electromagnet for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…Azizian et al 50 proposed a new approach, inspired by billiard ball collisions, for liquid marble manipulation by driving an FM to collide with a non-magnetic LM. Mohammadrashidi et al 51 experimentally investigated the dynamic behavior of ferrofluid liquid marbles on a solid substrate under magnetic fields, in which the LM undergoes discontinuous, less-controllable movement. Since LMs could be controlled on a solid surface or float on the water surface, [15][16][17][18] it has been demonstrated that marbles experience rolling when they are in contact with a solid surface, whereas floating marbles could undergo sliding motions, which is the preferred operating situation in DMF.…”
Section: Demonstrated That Magnetic Nanoparticles Have An Inhibitory ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Azizian et al 50 proposed a new approach, inspired by billiard ball collisions, for liquid marble manipulation by driving an FM to collide with a non-magnetic LM. Mohammadrashidi et al 51 experimentally investigated the dynamic behavior of ferrofluid liquid marbles on a solid substrate under magnetic fields, in which the LM undergoes discontinuous, less-controllable movement. Since LMs could be controlled on a solid surface or float on the water surface, [15][16][17][18] it has been demonstrated that marbles experience rolling when they are in contact with a solid surface, whereas floating marbles could undergo sliding motions, which is the preferred operating situation in DMF.…”
Section: Demonstrated That Magnetic Nanoparticles Have An Inhibitory ...mentioning
confidence: 99%
“…Unlike naked ferrofluid droplets, manipulating biocompatible LMs such as LMMSs is not fully understood, especially when they move on the water surface driven by a time-varying magnetic field. In this regard, FMs have attracted the attention of researchers more than LMMSs; 28,46,51 however, LMMSs could be preferable based on their higher biocompatibility, as magnetic nanoparticles and surfactants are in less contact with the biological cargo in the core fluid. 29,[54][55][56] The integration of electromagnets with a pulse-widthmodulation (PWM) circuit is promising as a stimulus for the manipulation of floating magnetic LMs.…”
Section: Demonstrated That Magnetic Nanoparticles Have An Inhibitory ...mentioning
confidence: 99%
“…While such “smart” machines can be actuated by different stimuli, magnetic fields appear to be particularly attractive for their precise controllability and efficacy in realizing a wide variety of shapes and functionalities. , The most common variant of such a micromachine can simply be a liquid drop made of a suspension of magnetic nanoparticles commonly known as ferrofluids. Despite being elusively simple to synthesize, the ferrofluids offer great promise in a wide variety of automated applications ranging from liquid cargo delivery, cell and tissue engineering, , water purification to on-chip mixing of liquid samples . Although their different shape modulations, splitting, and merging were successfully demonstrated in previous works, the proposition of tuning their wettability at will, preferably in a programmable manner, continues to offer an outstanding challenge when the applied field strength exceeds the saturation magnetization limit.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammadrashidi et al theoretically and experimentally studied the motion dynamics of ferrofluid marbles under steady and unsteady magnetic fields. They also observed the launching motion of ferrofluid marble by applying a single-pulse magnetic field . Azizian et al studied the collision of a ferrofluid marble with a water marble and examined the potential of using this collision for manipulating non-magnetic liquid marbles .…”
Section: Introductionmentioning
confidence: 99%
“…They also observed the launching motion of ferrofluid marble by applying a single-pulse magnetic field. 66 Azizian et al studied the collision of a ferrofluid marble with a water marble and examined the potential of using this collision for manipulating non-magnetic liquid marbles. 67 Yang et al investigated the reciprocating motion of ferrofluid marbles floating on the water surface.…”
Section: ■ Introductionmentioning
confidence: 99%